PENINGKATKAN MINAT DAN PRESTASI BELAJAR MATEMATIKA MENGGUNAKAN MODEL STUDENT TEAM ACHIEVEMENT DIVISION PADA SISWA KELAS VIIIC TAMAN DEWASA IBU PAWIYATAN YOGYAKARTA TAHUN PELAJARAN 2013/2014 - Noviana Yuliastuti; Benedictus Kusmanto (UNION: Jurnal Ilmiah Pendidikan Matematika, 2015)
The purpose of this research was to improve the interest and learning achievement in mathematic of student of class VIIIC Taman Dewasa Ibu Pawiyatan Yogyakarta using cooperatif learning type student team achievement division (STAD). The subjects of this research was student of class VIIIC Taman Dewasa Ibu Pawiyatan totaling 24 student. The object of this research was learning interest and mathematic learning achievement. The result showed that after application of using cooperatif learning student team achievement division (STAD) in class VIIIC Taman Dewasa Ibu Pawiyatan Yogyakarta, learning interest and mathematic learning achievement of student has increased. This was indicated by an increase in the result percentage average learning interest score of 69,098% in the pre-action, whereas at the first cycle improves with average percentage 70,834%. In the second cycle improve to 79,376%. Mathematic learning achievement of student also increased. At the beginning of the test the ability of students who meet the KKM is 37,50%. In the first cycle, the persentage increased to 45,83%. In the second cycle the percentage increased to 75,00%.